The effect of video-based instruction versus demonstration on learning of clinical skills - H.Karimi-Moneghi (M.Sc) (مجله دانشگاه علوم پزشکی گرگان, 2003)
Background & Objective: One of the most important principles in education is adopting a teaching method in concordance with objectives, contents and learners. Teaching and learning clinical skills is a challenging aspect of education in field of medicine and allied health profession. Some of the new researchers have shown that video-based instruction has many advantages in comparative to others. But in the domain of the psychomotor learning there is not enough evidence to show that video-based instruction is an effective teaching method. The current study has compared students learning in video-based and demonstration methods. Materials & Methods: An experimental study was conducted on 40 first year nursing and midwifery students. The students were randomly assigned to case (N=20) and control (N=20) groups based on the their course. The data were collected from a pre-test, a post-test and a questionnaire for demographic information. Pre-test was given 24 hours prior to the presentation sessions. Then each group has received one skill with video-based and another skill with demonstration. Skills included the dressing changing and surgical hand washing. After 24 hours post-test was taken with previous criteria. The differences between the pre-test and post-test scores were considered as they are at learning level. Results: The overall learning in the demonstration method was higher than the video-based method (P<0.05). However the scores of students in 2 methods was at acceptable level. The scores of students in the cognitive domain of hand washing by the demonstration were 16.20±1.5 and by the video-based method were 15.25±1. The scores of students in the psychomotor domain of hand washing by the demonstration was 16.85±1.4 and by the video-based method was 15.94±1.4 (P<0.05). The scores of students in the cognitive domain of dressing change by the demonstration was 25.60±1.8 and by the video-based method was 15.50±1. The scores of students in the psychomotor domain of dressing change by the demonstration was 16.78±1.3 and with the video-based was 16.12±1 (P<0.05). Conclusion: The results indicated that demonstration method is more effective in the students learning. However, both video-based and demonstration have led to the high level of cognitive and psychomotor learning. It could be concluded that video-based instruction can be an effective method for replacing the demonstration, especially when there is not access to demonstration, in addition according to the findings, video-based education is a effective methods for transporting knowledge, information and other topics in the cognitive domain. Therefore, considering the cost-effectiveness of video-based instruction and its ease of use, this method can facilitate education in where lack of experienced instructors and equipment is most pronounced.